2010
DOI: 10.1590/s1413-35552010005000014
|View full text |Cite
|
Sign up to set email alerts
|

The effects of knee extensor eccentric training on functional tests in healthy subjects

Abstract: Background: It is well known that eccentric training increases muscle strength and promotes greater neural activation, and therefore

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…Unfortunately, leg dominance was not revealed in this study. Second, Santos, Ávila, Hanashiro, Camargo, and Salvini (2010) observed that eccentric training not only improved The relationships of strength, power and balance 5 eccentric peak torque (at 30°s -1 and 120°s -1 ) of the knee extensors, but also increased distance achieved in both the single and triple hop test. It can be inferred that in the university group, greater relative eccentric strength of the knee extensors enabled the participants to achieve a greater normalised reach score, specifically when balancing on their non-dominant leg.…”
Section: Eccentric Strength Of the Knee Extensors And Dynamic Balancementioning
confidence: 93%
“…Unfortunately, leg dominance was not revealed in this study. Second, Santos, Ávila, Hanashiro, Camargo, and Salvini (2010) observed that eccentric training not only improved The relationships of strength, power and balance 5 eccentric peak torque (at 30°s -1 and 120°s -1 ) of the knee extensors, but also increased distance achieved in both the single and triple hop test. It can be inferred that in the university group, greater relative eccentric strength of the knee extensors enabled the participants to achieve a greater normalised reach score, specifically when balancing on their non-dominant leg.…”
Section: Eccentric Strength Of the Knee Extensors And Dynamic Balancementioning
confidence: 93%
“…Subjects were then asked to perform three maximal voluntary isometric contractions (MVICs) each lasting five seconds at intervals of 60 seconds [31]. …”
Section: Methodsmentioning
confidence: 99%
“…only fruit juice was allowed as breakfast, lunch, or dinner, 90 minutes before the testing session, and only a glass of water (200 ml) was allowed before taking the measurement. The subject warmed up on a stationary bicycle (75 W) for 5 minutes at the speed of 20 km/h; this was followed by a set of three 30-s stretches (with 30-s intervals) focused on knee flexors, knee extensors, and plantar flexors [25]. After that, the subjects were positioned in an isokinetic dynamometer with the backrest reclined 5° from the vertical plane and knees flexed at 90°.…”
Section: Methodsmentioning
confidence: 99%